Intramuscular tendon injuries of the hamstring muscles: a more severe variant? A narrative review - Kerin, F.; O`Flanagan, S.; Coyle, J.; Farrell, G.; Curley, D.; McCarthy Persson, U.; De Vito, G.; Delahunt, E. (Sports Medicine - Open, 2023)
Hamstring strain injuries (HSI) are one of the most common sport-related injuries. They have a high injury burden and a high recurrence rate. The development of novel muscle injury grading systems has provided new insights into the possible impact of injury location on the time to return to play (TTRTP) and re-injury following HSI. In particular, injuries to the intramuscular tendon (IMT) may be present in up to 41% of all HSI and have been described as a `serious thigh muscle strain`. Re-injury rates as high as 60% have been described in elite track and field athletes, as well as prolonged TTRTP. A systematic search was carried out using appropriate keywords to identify articles reporting on HSI involving the IMT in athletes. The primary aim was to determine whether IMT injuries warrant being classified as a distinct clinical entity with different expected outcomes to other hamstring muscle injuries. This narrative review summarises the existing evidence on: (1) the anatomy of the IMT and its response to injury; (2) the role of MRI and novel grading scales in IMT injury management (3) clinical assessment of IMT injuries, (4) TTRTP and re-injury rates across sports following IMT, (5) conservative rehabilitation and the role of specific `IMT-oriented` strategies, and (6) indications for and approaches to surgery. The review found that important clinical outcomes such as re-injury rates and TTRTP vary across populations, cohorts and sports which suggest that outcomes are specific to the sporting context. Bespoke rehabilitation, tailored to IMT injury, has been shown to significantly reduce re-injuries in elite track and field athletes, without compromising TTRTP. Continued prospective studies across other sports and cohorts, are warranted to further establish relevant clinical findings, indications for surgical intervention and outcomes across other sporting cohorts.